Faktor - Faktor yang Memengaruhi Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual pada Biro Keuangan dan BMN Seketariat Jenderal Kemendikbud Ristek - Faisal, Alif; Pahala, Indra; Utaminingtyas, Tri Hesti (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This research was conducted with the aim of obtaining empirical evidence regarding the Quality of Human Resources, Organizational Commitment, and Information Technology on the Application of Accrual-Based Government Accounting Standards. This study uses primary data with a sample of employees of the Bureau of Finance and BMN at the Ministry of Education and Culture. The sampling technique in this study used convenience sampling with 98 respondents. Testing the hypothesis in this study uses a multiple regression model using SPSS 25. Based on the results of the analysis in this study, it can be concluded that: (1) the quality of human resources has a significant positive effect on the application of accrual-based government accounting standards, (2) organizational commitment has a significant positive effect on the application of accrual-based government accounting standards, and ( 3) information technology has a significant positive influence on the application of accrual-based government accounting standards. Thus, the increasing of each of the variables of the quality of human resources, organizational commitment, and information technology, then each of these independent variables will be able to increase the application of accrual-based government accounting standards.